An Optimized/Scale Up-Ready Protocol for Extraction of Bacterially Produced dsRNA at Good Yield and Low Costs - Figueiredo Prates, Lucas Henrique; Merlau, Maximilian; Rühl-Teichner, Johanna; Schetelig, Marc F.; Häcker, Irina; Justus Liebig University Giessen (My University, 2023)
Double-stranded RNA (dsRNA) can trigger RNA interference (RNAi) and lead to directed silencing of specific genes. This natural defense mechanism and RNA-based products have been explored for their potential as a sustainable and ecofriendly alternative for pest control of species of agricultural importance and disease vectors. Yet, further research, development of new products and possible applications require a cost-efficient production of dsRNA. In vivo transcription of dsRNA in bacterial cells has been widely used as a versatile and inducible system for production of dsRNA combined with a purification step required to extract the dsRNA. Here, we optimized an acidic phenol-based protocol for extraction of bacterially produced dsRNA at low cost and good yield. In this protocol, bacterial cells are efficiently lysed, with no viable bacterial cells present in the downstream steps of the purification. Furthermore, we performed a comparative dsRNA quality and yield assessment of our optimized protocol and other protocols available in the literature and confirmed the cost-efficiency of our optimized protocol by comparing the cost of extraction and yields of each extraction method.
Keywords: double-stranded RNA; bacterial production system; RNA interference; RNAi-based pest control; dsRNA production costs; RNA-based biopesticides; organic purification; liquid–liquid extraction; selective extraction; ddc:630